Strength and power predictors of swimming starts in international sprint swimmers - West, D. J.; Owen, N. J.; Cunningham, D. J.; Cook, C. J.; Kilduff, L. P. (The Journal of Strength and Conditioning Research, 2011)
Start performance (as defined by time to 15 m) has been shown to be a key performance indicator during 50-m freestyle swimming; however, there is limited information with regard to the key strength and power variables that influence start performance during sprint swimming. In light of the above, this study aimed to examine the key strength and power predicators of start performance in 50-m freestyle swimming. Eleven male British international sprint swimmers (age 21.3 ± 1.7 years; mass 78.1 ± 11.2 kg; and height 1.8 ± 0.1 m) participated in this study. Within 1 week, swimmers performed the following tests: 3 repetition maximum (3RM) squat strength, countermovement jump (CMJ) on a portable force platform, and a measure of start time performance (time to 15 m under 50-m freestyle conditions). The start time was measured using a standard racing platform to which a portable force platform was mounted, and all starts were recorded using 2 cameras. This setup allowed for the quantification of time to 15 m, peak vertical force (PVF), and peak horizontal force (PHF). Data were analyzed using Pearson's product moment correlation with significance set at p < 0.05. Start time was significantly related to 1RM strength (r = -0.74), jump height (r = -0.69), peak (r = -0.85), and relative power (r = -0.66) (p < 0.05) but not rate of force development (r = -0.56, p > 0.05). Furthermore, lower body strength was a key determinant of jump height (r = 0.69), power (r = 0.78), PVF (r = 0.62), and PHF (r = 0.71) (p < 0.05). This study provides evidence of the importance of lower body strength and power to start time in international 50-m sprint swimmers.